2003
DOI: 10.1080/13504850210161887
|View full text |Cite
|
Sign up to set email alerts
|

A semiparametric investigation of the school quality-gs relationship

Abstract: This article estimates a partially linear model that permits non-linearities of unspecified form in the school quality-earnings relationship. It examines the joint effect of teacher education and pupil-teacher ratios on 1990 earnings using NLSY data. It finds some evidence of non-linearities in this relationship, and that teacher education has a positive effect on log wages at some points in the pupil-teacher ratio support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For example,Angrist and Lavy (1999),Krueger (1999) andMcKee et al (2010) showed positive effects on the outcomes from lower student-to-teacher ratios, and Lin (2009),Li and Tobias (2003),Strauss and Sawyer (1986),Ferguson (1991) andEhrenberg and Brewer (1994) found similar outcomes from increases in teachers' aptitude scores. 2 Several studies investigate the cost-effectiveness in education (see e.g Levin, 1970;Summers and Wolfe, 1977;Levin, 1988;Yeh, 2010)…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…For example,Angrist and Lavy (1999),Krueger (1999) andMcKee et al (2010) showed positive effects on the outcomes from lower student-to-teacher ratios, and Lin (2009),Li and Tobias (2003),Strauss and Sawyer (1986),Ferguson (1991) andEhrenberg and Brewer (1994) found similar outcomes from increases in teachers' aptitude scores. 2 Several studies investigate the cost-effectiveness in education (see e.g Levin, 1970;Summers and Wolfe, 1977;Levin, 1988;Yeh, 2010)…”
mentioning
confidence: 71%
“…The primary data for this study are from the restricted-access versions of the 1999-2000, 2003-2004and the 2007-2008. Teacher quality is measured as a teacher's scholastic aptitude in percentiles and is constructed using restricted-access versions of the National Post-Secondary Aid Survey (NPSAS).…”
Section: Data and Empirical Specificationmentioning
confidence: 99%
“…The educational qualification and wages were identified to be positively correlated with PTR [42]. Highly skilled teachers are normally assigned to big classes for the purposes of maximum impact and return on investment.…”
Section: Effect Of Ptr On Teachersmentioning
confidence: 99%